Characterization of carbon-composite antennas for wireless charging. Issue 1 (18th December 2018) - Ciccarelli, Lucas Anthony; Breckenfelder, Christof; Greb, Christoph
Abstract : The objective of the presented work is to take advantage of the precision capabilities of tailor-fiber-placement (TFP) embroidery processes in order to qualify carbon-fiber parts as viable antennas for wireless power transfer applications in multifunctional carbon-fiber-reinforced plastic (CFRP) composites. The solution comes first from a literature study of electrical, high-frequency, and textile engineering concepts. This review built familiarity with the technological challenges and state-of-the-art of the presented technology. Next step was iterative experimentation of machine capabilities for the production of carbon-fiber antennas. Finally, antenna prototypes were produced and their physical and electrical characteristics were evaluated through several test methods. The results showed that TFP embroidery machines were capable of producing quality, carbon antennas. Induction values of the antennas from 0.5 to 3.5 'H were achieved. Signal transfer efficiencies from carbon-antenna transmitters to an aftermarket receiver show promise in commercial application.